Peran Roh Kudus Sebagai Allah yang Personal di dalam Gereja - Sihombing, Edy Syahputra (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
The Holy Spirit in Christianity is portrayed as God who exists actively through human experiences. The presence of the Holy Spirit who dwells in human’s heart is a unique presence of one of the Persons of the Trinity. However, the Holy Spirit’s presence in human experiences is not always identified as the ‘Person’ of God. Here the language of dogmatic theology might not be clear and inspiring to Christians to recognise the unique presence of the Holy Spirit in their hearts and in the living of faith in the Church. There is a need to contemplate the aspects of human personal experience of the Holy Spirit in relation to the theological language of the Persons in Trinity so that the faithful may discern the presence of the Holy Spirit in their lives. It is therefore important that in theological discussions about the Holy Spirit there is an awareness to view the need of ‘translating’ theological language into simpler language of catechism. In order that the faithful are able to identify the presence and the works of the Holy Spirit in experiences, in prayer, and in the life of faith, catechetical language about the Holy Spirit should bring more images related to human experience.